Odpowiedzi

Najlepsza Odpowiedź!
2010-02-03T20:36:05+01:00
A)
18x²+6x = 6x(3x+1)
b)
47m²-19m = m(47m-19)
c)
-12kl+30k²l² = 3kl(-4+10kl)
d)
16xyz-48xy+60yz = 4y(4xz-12x+15z)
e)
50x²y+60xy²-70xy = 10xy(5x+6y-7)
f)
21x⁴-35x³+63x²-14x+7 = 7(3x⁴-5x³+9x²-2x+1)
g)
k⁴m⁶-k²m⁵+k³m³ = km(k³m⁵-km⁴+k²m²)
h)
-54b⁴-27b³-9b²-36 = 9(-6b⁴-3b³-b²-4)
2010-02-03T20:46:17+01:00
A)) = 6x(3x+1)
b)) = m(47m-19)
c)) = -6kl(2-5kl)
d)) = 4y(4xz-12x+15z)
e)) = 10xy(5x+6y-7)
f)) = 7(3x⁴-5x³+9x²+z)
g)) = k²m³(km⁴-m²+k)
h)) = 9(-6b⁴-3b³-b²-4)